Assessment of Women Satisfaction with Pregnancy Outcome and Using of Immediate Contraceptive Postnatal at Baghdad Maternity Hospitals - Sarah Kifah Jaafar (Pakistan Journal of Medical & Health Sciences, 2022)
Back ground: Contraceptive following delivery or an induced abortion reduces the risk of an early unintended pregnancy and it’s associated to adverse health consequences The Study aims to assess the women satisfaction in the use of contraceptive devices in the period immediately following delivery or abortion and it’s relation to pregnancy outcome. Patients and Methodology: A randomized cross sectional descriptive study carried out In 2 maternity hospitals (AL-Elwiya maternity teaching hospital, AL-Karkh maternity hospital) from both sides of Baghdad. The study sample includes 434 cases of women who were in the labor and abortion wards in the period immediately following delivery or abortion before being discharged home. Data were collected during the period from the 1st of November 2015 to the end of April 2016. Results: revealed that more than half (54.4%) of studied women were married in young age group (18-24 years) and 48.6% of them were at young age (18-24 years) at their first delivery, 36.4% were graduated from university, (90.3%) were living in urban areas . The pregnancy ended with delivery in 65.2% of the studied women and ended with miscarriage in 34.8% of them. A significant association was observed between young age of women and high satisfaction with immediate contraception (p=0.02). The most common cause of non-satisfaction with contraception among studied women was not knowing about the possibility of contraception (97.67%), followed by their wish to increase their family size (39.5%), fear from complications (23.2%), economic causes (18.6%), un cooperation of the family (13.9%), bad effect on breast feeding (9.3%) and unavailability (6.9%). one third (31.1%) of the participants were satisfied with immediate contraception while it is about half (49.1%) of the delivered mothers were satisfied on immediate contraceptive with significant difference found between pregnancy outcome and the women’s satisfaction. Conclusion: 49.1% of the mothers were satisfied on immediate contraception after delivery while only 31.1% of the miscarried women were satisfied with immediate contraception. Women from low income families had higher satisfaction with contraception and significant association was found between types of pregnancy outcome and women satisfaction with immediate use of contraceptive devices. Keywords: Assessment, Women Satisfaction, Pregnancy Outcome, Immediate Contraceptive, Postnatal